2021
DOI: 10.1371/journal.pcbi.1009690
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale model for forecasting Sabin 2 vaccine virus household and community transmission

Abstract: Since the global withdrawal of Sabin 2 oral poliovirus vaccine (OPV) from routine immunization, the Global Polio Eradication Initiative (GPEI) has reported multiple circulating vaccine-derived poliovirus type 2 (cVDPV2) outbreaks. Here, we generated an agent-based, mechanistic model designed to assess OPV-related vaccine virus transmission risk in populations with heterogeneous immunity, demography, and social mixing patterns. To showcase the utility of our model, we present a simulation of mOPV2-related Sabin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Of these, 24/29 (82.8%) actually shared code, 29/33 (87.9%) actually shared data and 5/6 (83.3%) were indeed registered. The papers that used registration were two malaria models [24,25], one vector model [26] (which focused on malaria vectors) one polio (Sabin 2 virus [27]) model and one rotavirus model [28]. The majority were from 2021 [24,26,27] and were also malaria models (two malaria and one vector that was essentially malaria [24][25][26]).…”
Section: Manual Validationmentioning
confidence: 99%
“…Of these, 24/29 (82.8%) actually shared code, 29/33 (87.9%) actually shared data and 5/6 (83.3%) were indeed registered. The papers that used registration were two malaria models [24,25], one vector model [26] (which focused on malaria vectors) one polio (Sabin 2 virus [27]) model and one rotavirus model [28]. The majority were from 2021 [24,26,27] and were also malaria models (two malaria and one vector that was essentially malaria [24][25][26]).…”
Section: Manual Validationmentioning
confidence: 99%
“…Of these, 24/29 (82.8%) actually shared code, 29/33 (87.9%) actually shared data and 5/6 (83.3%) were indeed registered. The papers that used registration were two malaria models(14,15), one vector model (16) (which focused on malaria vectors) one polio (Sabin 2 virus (17)) model and one rotavirus model(18). The majority were from 2021(14,16,17) and were also malaria models (two malaria and one vector that was essentially malaria (1416)) the majority we also classified as spatiotemporal (1416).…”
Section: Resultsmentioning
confidence: 99%
“…The papers that used registration were two malaria models(14,15), one vector model (16) (which focused on malaria vectors) one polio (Sabin 2 virus (17)) model and one rotavirus model(18). The majority were from 2021(14,16,17) and were also malaria models (two malaria and one vector that was essentially malaria (1416)) the majority we also classified as spatiotemporal (1416). Finally, of the 120 articles (10%) that text mining found that they contained a COI statements, there was indeed a placeholder for this ststement in all articles, but the vast majority of the statements (115 (95.8%)) disclosed no conflict at all.…”
Section: Resultsmentioning
confidence: 99%
“…For a mechanistic model of oral poliovirus-related vaccine virus transmission risk, optimal model parameters were identified with Latin hypercube sampling and a pseudo-likelihood function to minimize the discrepancy between simulated and observed data (Famulare et al. 2021 ).…”
Section: Discussionmentioning
confidence: 99%